2015
DOI: 10.5223/pghn.2015.18.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Metabolic Liver Disease: Experience at a Living Donor Dominant Liver Transplantation Center

Abstract: PurposeMetabolic liver disease (MLD) often progresses to life-threatening conditions. This study intends to describe the outcomes of liver transplantation (LTx) for MLD at a living donor-dominant transplantation center where potentially heterozygous carrier grafts are employed.MethodsWe retrospectively evaluated the medical records of 54 patients with MLD who underwent LTx between November 1995 and February 2012 at Asan Medical Center in Seoul, Korea. The cumulative graft and patient survival rates were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 24 publications
4
19
1
Order By: Relevance
“…Arnon et al (21) showed that survival rates of their patients with metabolic and non-metabolic diseases were 94.6% and 90.7% at one year respectively and 88.9% and 86.1% respectively at year five. The cumulative survival rates in pediatric patients with non-metabolic disease were 91.9%, 87.2%, and 85.8% at one, five, and 10 years, respectively (22). The survival rate was lower in both the metabolic and non-metabolic disease groups in our study, which was different from the study by Kayler et al (15).…”
Section: Discussioncontrasting
confidence: 92%
“…Arnon et al (21) showed that survival rates of their patients with metabolic and non-metabolic diseases were 94.6% and 90.7% at one year respectively and 88.9% and 86.1% respectively at year five. The cumulative survival rates in pediatric patients with non-metabolic disease were 91.9%, 87.2%, and 85.8% at one, five, and 10 years, respectively (22). The survival rate was lower in both the metabolic and non-metabolic disease groups in our study, which was different from the study by Kayler et al (15).…”
Section: Discussioncontrasting
confidence: 92%
“…In children with citrullinemia who have recovered from the initial presentation and have a subsequent period of stability, the indication and timing of LT need to be carefully considered within a multidisciplinary setting. Kim et al reported a mean age of LT in neonatal‐onset citrullinemia of 1.7 years (range, 0.8‐5.25), which is comparable to our group. Surgical and infectious complications post‐LT tend to be less frequent with increasing age of the child .…”
Section: Discussionsupporting
confidence: 89%
“…The use of heterozygote donors for some children with metabolic disorders is well documented . The overall experience is positive with adequate enzyme replacement despite using a carrier donor .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of enzymatic testing, there were no observed mortality or morbidity related to recurrence of disease with the use of heterozygotes in all studied donors and recipients. This is consistent with other small cohorts utilizing heterozygote donors for metabolic liver disease . The common findings in all utilized heterozygote donors are the lack of symptoms related to the given disease and normal ammonia and amino acid levels, despite decreased enzymatic activity.…”
Section: Heterozygote Donorssupporting
confidence: 89%